Innovation of Portable Tectonic Earthquake Detection System with Arduino Uno: An Affordable Early Warning System Solution - Hamidah, Selfi Nur; Putri, Davina Razaktya Kayla; Rizqullah, Muhammad Kalvin Al Azhaar; Urrofiqoh, Syita; Hawa, Asfa Malia; Nurita, Tutut; Widodo, Wahono (Diponegoro University Semarang Indonesia, 2025)
Indonesia, located in a highly seismic region due to the convergence of the Indo-Australian, Eurasian, and Pacific plates, requires affordable earthquake early warning systems. This research aims to develop an easy-to-use, portable tectonic earthquake detection system based on the Arduino Uno platform. The methodology encompassed the design of hardware and software, the installation of accelerometer sensors, and the programming of the Arduino to detect ground vibration intensity. Test results demonstrate that the system is sensitive to changes in vibration and can provide an audible warning via a buzzer when a predefined vibration threshold is exceeded. Although its accuracy is lower than that of professional seismographs, the system presents an economical solution for deployment in remote areas. Future development could incorporate GPS sensors and artificial intelligence to enhance its accuracy and expand its applicability across various disaster scenarios.